Outcomes from an infectious disease physician-guided evaluation of hospitalized persons under investigation for coronavirus disease 2019 (COVID-19) at a large US academic medical center. (24th March 2021) - Dugdale, Caitlin M.; Turbett, Sarah E.; McCluskey, Suzanne M.; Zachary, Kimon C.; Shenoy, Erica S.; Ciaranello, Andrea L.; Walensky, Rochelle P.; Rosenberg, Eric S.; Anahtar, Melis N.; Hooper, David C.; Hyle, Emily P.
Abstract: We describe an approach to the evaluation and isolation of hospitalized persons under investigation (PUIs) for coronavirus disease 2019 (COVID-19) at a large US academic medical center. Only a small proportion (2.9%) of PUIs with 1 or more repeated severe acute respiratory coronavirus virus 2 (SARS-CoV-2) nucleic acid amplification tests (NAATs) after a negative NAAT were diagnosed with COVID-19.